The endless question: why (should I) act morally?: analysis of chapter 12 of Practical Ethics by Peter Singer - Castro, Paulo Alexandre e (2024)
This essay seeks to provide a detailed analysis of chapter 12 of Peter Singer's Practical Ethics. Fundamental chapter not only for understanding the author's ethical and moral thought, but also for understanding the author's cultural and civilizational thought. It is in this sense that the question posed in the title - why act morally - is not limited to the horizon of the redundant discussion of personal interest or educational factors but becomes the philosophical-ethical exercise of inquiry into human action in the world, and therefore, It is a question that is rooted within ethics itself (as the author states), that is, as the foundation of human action. The essay ends with a reflection on the validity of the author’s ethical thinking in this specific chapter and some considerations on the philosopher’s general ethical thought.